Political regimes and the conditions for development-oriented state intervention : a theoretical and comparative perspective with reference to South Africa - Luiz, John Manuel (Stellenbosch : Stellenbosch University, 2012)
Dissertations (Ph. D.) -- University of Stellenbosch, 1998.